Photographie et maquette chez Le Corbusier. Dialogues entre la création et la diffusion. - Miguel-Angel de La Cova (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
From Villa Fallet in 1907 to Venice Hospital in 1965, Le Corbusier created architectural models and photographed them, either to be used as media devices or working tools. Photography and architectural modelling therefore serve as actors in both scenes that characterize the architect’s career: his workshops and media forums. Through his intent as well as the work of his photographers and model-makers, who were close collaborators of the architect, Le Corbusier’s photos unite the private and public realms, as well as the self and the other. The different photographic frames demonstrate the use of architectural models as beyond just a simulation of the future building. To what extent is the model built and prepared to be photographed? Heavily related to this are the chosen backgrounds, the bases in which they placed scaled objects to be photographed, the selection of materials and colours to build the models as well as the way they were built. How is the camera placed in front of the model? What is it searching for? Since the camera is placed in several positions and heights in front of the model, attention should be given to the relationship between photographs of the model and more traditional drawing perspectives. There seems to be a dialogue between both tools – the model and the camera – from which a piece of architecture is analysed and revealed. At the same time, the object itself emerges as a work of art, creating a dialogue that goes beyond simulation boundaries and that delves into artistic discourse.